HUMAN RESOURCE MANAGEMENT STRATEGY TO INCREASE ECONOMIC PRODUCTIVITY IN THE DIGITAL ERA - Fepi Leisthari; Shally Rizkiyanti; Hidayah Aprini (Adisam Publisher, 2025)
Effective human resource management strategies in the digital era play a crucial role in increasing economic productivity. This article discusses the importance of digital skills development, work culture transformation, and technology adoption in HR management. Investment in digital training enables the workforce to stay relevant to market needs, while an innovative and flexible work culture drives productivity and work-life balance. In addition, the use of technologies such as human resource management systems and data analytics provides significant operational efficiencies. Implementing these strategies also requires adaptive leadership that is able to inspire teams and encourage cross-functional collaboration. While there are challenges, such as skills gaps and technology access, a holistic approach involving various stakeholders can help overcome these obstacles. This article concludes that digital-based human resource strategies not only increase organizational competitiveness but also have a positive impact on society, create more inclusive employment opportunities, and drive sustainable economic growth.